INTERNATIONALIZATION OF ECONOMIC ACTIVITIES AND GOVERNMENT’S INVOLVEMENT IN THE MARKET ECONOMY - ŢÂU, Nicolae (Annals of Spiru Haret University. Economic Series, 2017)
Expanding economic relations and creating an international business environment, international business and the internationalization of the commercial transactions across national borders have become a prerequisite for companies, regardless of the activity they carry. Thus, internationalization is seen as a set of strategic methods, techniques and tools necessary to the companies to function abroad. As the effects of – fiscal and monetary – policies on the global demand and supply are unpredictable in time and space, it appears the requirement to substantiate, develop and put into practice a stabilizing strategy. Besides the indexes showing the evolution of the demand and supply, the market can offer economic agents other analysis and decision parameters as well, such as: economic and financial instruments for influencing the behaviour of the business environment.Obviously, the results depend also on how the authorities (legislative and executive, central and local) work for a friendly business environment. There are two mechanisms that can be used for this purpose: fiscal policy (measures to enhance or reduce taxes, dues and public spending) initiated by the Government and approved by Parliament; monetary policy (setting the interest rate and the money supply, respectively of the money stock for a specified period of time) emitted and monitored (supervised) by the National Bank.